2015
DOI: 10.1128/aem.02633-14
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Biocides: Efficacy in Application

Abstract: Quaternary ammonium compounds (QACs) are among the most commonly used disinfectants. There has been concern that their widespread use will lead to the development of resistant organisms, and it has been suggested that limits should be place on their use. While increases in tolerance to QACs have been observed, there is no clear evidence to support the development of resistance to QACs. Since efflux pumps are believe to account for at least some of the increased tolerance found in bacteria, there has been conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
340
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 462 publications
(360 citation statements)
references
References 47 publications
5
340
1
14
Order By: Relevance
“…In clinical health issues like treatments of infections, aminoglycosides and quinolones were reported to be effective (3,9), while public health issues have been countered with surfactants and sanitizers, like quaternary ammonium compounds (10). However, we found that Methylobacterium strains isolated from bathrooms were tolerant to various stresses, including surfactants like benzalkonium chloride (BAC) (8,11).…”
contrasting
confidence: 38%
“…In clinical health issues like treatments of infections, aminoglycosides and quinolones were reported to be effective (3,9), while public health issues have been countered with surfactants and sanitizers, like quaternary ammonium compounds (10). However, we found that Methylobacterium strains isolated from bathrooms were tolerant to various stresses, including surfactants like benzalkonium chloride (BAC) (8,11).…”
contrasting
confidence: 38%
“…Additionally, quaternary ammonium compounds have been used as hard surface sanitizers and disinfectants for more than 70 years. They are particularly effective against a wide range of bacteria and lipidcontaining viruses (Gerba 2015), although they can be formulated to be effective against non-lipid viruses such as norovirus (Gerba 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Disinfectants and antiseptics are widely used in hospitals and other health care centers as a type of topical and hard-surface practices. Especially, they are a necessary portion of infection control programs and help prevent nosocomial infections (8,9). The quaternary ammonium compounds (qacs) and small multidrug-resistance (smr) genes are responsible for resistance to antiseptics (10).…”
Section: Introductionmentioning
confidence: 99%